2016
DOI: 10.3390/ijms17091566
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Galectin-1 in Cancer Progression, and Synthetic Multivalent Systems for the Study of Galectin-1

Abstract: This review discusses the role of galectin-1 in the tumor microenvironment. First, the structure and function of galectin-1 are discussed. Galectin-1, a member of the galectin family of lectins, is a functionally dimeric galactoside-binding protein. Although galectin-1 has both intracellular and extracellular functions, the defining carbohydrate-binding role occurs extracellularly. In this review, the extracellular roles of galectin-1 in cancer processes are discussed. In particular, the importance of multival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
95
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(99 citation statements)
references
References 151 publications
(257 reference statements)
3
95
0
1
Order By: Relevance
“…One soluble protein known to induce CD8 + T cell apoptosis is Galectin‐1. Produced by tumor cells, Galectin‐1 can bind the Galβ1‐4GlcNAc (LacNAc) epitope, which is elevated in our MC38‐Sia null cells after removal of the Sia. Galectin‐1 supports tumor progression through cell–cell and cell‐matrix interactions as well as tumor‐induced angiogenesis and an elevated CD8 + T cell apoptosis .…”
Section: Discussionmentioning
confidence: 95%
“…One soluble protein known to induce CD8 + T cell apoptosis is Galectin‐1. Produced by tumor cells, Galectin‐1 can bind the Galβ1‐4GlcNAc (LacNAc) epitope, which is elevated in our MC38‐Sia null cells after removal of the Sia. Galectin‐1 supports tumor progression through cell–cell and cell‐matrix interactions as well as tumor‐induced angiogenesis and an elevated CD8 + T cell apoptosis .…”
Section: Discussionmentioning
confidence: 95%
“…Recently, a study suggested that total absence of Gal-1 in the bone microenvironment allows rapid development of bone tumors [39]. Increased expression of Gal-1 has been correlated with a variety of processes in cancer progression, including cellular aggregation, tumor formation, the metastatic spread of cancer, angiogenesis, and apoptosis [40]. OPN and BSPII belong to a family of glycoproteins that have been linked to cancer metastasis and progression and are overexpressed in a variety of cancers, including lung cancer, breast cancer, colorectal cancer, stomach cancer, ovarian cancer, papillary thyroid carcinoma, melanoma and pleural mesothelioma [41,42].…”
Section: Plos Onementioning
confidence: 99%
“…Gal-1 can mediate neoplastic transformation by interacting with oncogenes, such as H-Ras and promote Ras-mediated signal transduction involving RAF1 and extracellular signal-regulated kinase (ERK). Gal-1 multivalently mediates tumor cell-ECM adhesion at the primary site by cross-linking cell surface glycoproteins, such as integrins, and glycosylated proteins in the ECM, such as laminin and fibronectin [28]. Hence, Gal-1 is regarded as a promising molecular target for the development of new therapeutic drugs for cancer.…”
Section: Target-based Benzimidazole Derivatives 31 Galectin-1 Inhibimentioning
confidence: 99%